Safety and Efficacy of Low Molecular Weight Dextran (Dextran 40) in Head and Neck Free Flap Reconstruction - Jayaprasad, Kiran; Mathew, Jimmy; Thankappan, Krishnakumar; Sharma, Mohit; Duraisamy, Sriprakash; Rajan, Sunil; Paul, Jerry; Iyer, Subramania (Journal of Reconstructive Microsurgery, 2013)
Background Antithrombotic agents have been used in microvascular surgeries. Low molecular weight dextran (dextran 40), though used, is not without complications.Methods Retrospective analysis of 172 consecutive flaps. A comparison was made between two groups of patients (86 flaps each) with and without the use of dextran 40, in terms of safety and efficacy.Results The free flap survival rate was 95.9%. The flap survival rates were comparable between the groups. Total flap loss in Group A (patients who received dextran 40) was 3.5% compared with 2.3% in Group B (patients who did not receive dextran 40) (p = 1.00). There was no statistically significant difference in the incidence of thrombotic flap complications between the groups. None of the patients developed acute respiratory distress syndrome or required prolonged ventilator support. No patient had dextran-related anaphylactoid reactions. Thirty-eight patients (43.7%) in Group A had postoperative atelectasis and 21 (25.6%) patients in Group B had this complication (p = 0.01). Six patients in Group A developed postoperative pneumonia, and five patients in Group B developed this complication (p = 0.93).Conclusions Though dextran 40 did not result in any significant adverse local or systemic complications, it is not useful as a postoperative antithrombotic agent in head and neck oncologic reconstruction with free tissue transfer.
Keywords: low molecular weight dextran; head and neck reconstruction; free flaps; flap survival; thrombosis